Intranasal corticosteroids for the medical management of nasal polyps in adults a meta-analysis - Aguilar, Natividad Almazan-
OBJECTIVES: to determine the efficacy of short term (2-4 weeks) and long term duration (4-12 weeks and more) of intranasal corticosteroids in the reduction of polyp size and rhinitis symptoms of nasal polyps in adults. To determine whether there is a difference in efficacy of a 400 ug vs an 800 ug dose and to determine the common adverse side effects of intranasal steroids. STUDY DESIGN: Meta-analysis of randomized controlled trials on intranasal steroids for nasal polyps. SEARCH STRATEGY: Comprehensive search of Cochrane's Controlled Trials Registry (CCTR), Medline and Embase. Bibliographic review and requests for information from study authors and pharmaceutical companies supplemented this. SELECTION CRITERIA: Only randomized controlled trials (RCTs) evaluating intranasal steroid treatment compared with placebo for adults with nasal polyps were included irrespective of publication status. Patient-oriented outcomes considered most relevant were reduction of polyp size and overall reduction of rhinitis symptoms that included nasal obstruction, nasal discharge, itchiness and sneezing as well as medication side effects. DATA COLLECTION AND ANALYSIS: Investigators independently evaluated studies for inclusion, performed trial quality and validity assessments and completed data extraction. The ordinal data on rhinitis score and polyp score for each study included were combined by making a new criterion: with reduction or without reduction in polyp size and rhinitis symptoms. These new dichotomous data were pooled to generate relative risks. Homogeneity among studies was assessed using approximate chi-square tests. A prest p value of <0.10 was deemed significant for heterogeneity. Data were analyzed using software program Revman 4.1. Sensitivity analysis was done for those outcomes with significant heterogeneity. MAIN RESULTS: Of the 88 potentially relevant studies, 16 were included in the review with a total number of 1170 adults with nasal polyps. Pooled results of 14 studies found significant benefit in the use of intranasal steroids for nasal polyps on adults in the reduction of polyp size with 2 to 4 weeks treatment (RR=3.00; 95%CI: 2.39, 3.77). Overall rhinitis symptoms decreased significantly in pooled analysis of 4 studies, (RR=1.64; 95%CI: 1.25, 2.14) with 4-12 weeks duration of intranasal steroids compared to placebo treatment. Two studies with more than 12 weeks treatment showed tendency for reduction of rhinitis symptoms with intranasal steroids as compared to placebo (RR=1.41; 95%CI: 1.05, 1.91). Throat irritation was significantly increased with intranasal use than placebo (RR=2.06; 95%CI: 1.31, 3.25). Nasal itchiness showed no significant difference in both the intranasal steroids and placebo groups (RR=1.33; 95%CI: 1.72, 2.45). Pooled results of three studies comparing the 400 ug and 800 ug dose intranasal steroids showed no difference in overall rhinitis symptoms (RR=0.91: 95%CI: 0.77, 1.07). The following comparisons of outcome measures had significant heterogeneity and no conclusions were made: 1) 12 studies on 2-4 weeks treatment in the reduction of overall rhinitis symptoms, 2) 4 studies on 4-12 weeks treatment in reduction of polyp, 3) 3 studies on dose effect of 400 ug vs 800 ug in the reduction of polyp size and 4) 7 studies on epistaxis. CONCLUSIONS: Intranasal corticosteroids conferred significant benefit in decrease of the size of polyps at 2-4 weeks treatment. Rhinitis symptoms were reduced when treatment was used for a longer period of more than 4 weeks and more than 12 weeks. The adverse effect of throat irritation was significantly seen with intranasal steroid use and nasal itchiness was seen in both the intranasal steroids and placebo group. There was no significant difference in overall rhinitis symptoms with the 400 ug dose and the 800 ug dose of intranasal steroids.